Entrepreneurial citizenship: Crafting good and smart ventures with civic character - Trihastuti, Meiwatizal; Pranata, Bimo (Universitas Negeri Yogyakarta, 2025)
This study examines the concept of entrepreneurial citizenship and how it shapes entrepreneurs who embody both integrity and business acumen within the context of citizenship. Employing a qualitative approach with case study methodology, this research explores how the characteristics of civic entrepreneurs contribute to the development of business leaders who integrate civic values with entrepreneurial intelligence. Data collection methods include in-depth interviews with entrepreneurs exhibiting strong entrepreneurial citizenship attributes, participant observation, and the analysis of relevant documents. The findings reveal that entrepreneurs who adopt the principles of entrepreneurial citizenship tend to demonstrate a heightened awareness of social and environmental responsibility, uphold ethical business practices, and engage in sustainable innovation. Furthermore, they actively collaborate with stakeholders across various sectors to generate broader positive impacts on society. These insights contribute value to the discourse on implementing entrepreneurial citizenship to foster sustainable and socially meaningful entrepreneurship. The practical implications of this research include recommendations for entrepreneurship education that is more aligned with civic values, policy support to enhance collaboration between the business and government sectors, and the promotion of an organisational culture that prioritises integrity and social responsibility.